Anesthetic technique for inferior alveolar nerve block: a new approach - Dafna Geller Palti; Cristiane Machado de Almeida; Antonio de Castro Rodrigues; Jesus Carlos Andreo; José Eduardo Oliveira Lima (University of São Paulo, 2011)
BACKGROUND: Effective pain control in Dentistry may be achieved by local anesthetic techniques. The success of the anesthetic technique in mandibular structures depends on the proximity of the needle tip to the mandibular foramen at the moment of anesthetic injection into the pterygomandibular region. Two techniques are available to reach the inferior alveolar nerve where it enters the mandibular canal, namely indirect and direct; these techniques differ in the number of movements required. Data demonstrate that the indirect technique is considered ineffective in 15% of cases and the direct technique in 13-29% of cases. OBJECTIVE: The aim of this study was to describe an alternative technique for inferior alveolar nerve block using several anatomical points for reference, simplifying the procedure and enabling greater success and a more rapid learning curve. MATERIAL AND METHODS: A total of 193 mandibles (146 with permanent dentition and 47 with primary dentition) from dry skulls were used to establish a relationship between the teeth and the mandibular foramen. By using two wires, the first passing through the mesiobuccal groove and middle point of the mesial slope of the distolingual cusp of the primary second molar or permanent first molar (right side), and the second following the oclusal plane (left side), a line can be achieved whose projection coincides with the left mandibular foramen. RESULTS: The obtained data showed correlation in 82.88% of cases using the permanent first molar, and in 93.62% of cases using the primary second molar. CONCLUSION: This method is potentially effective for inferior alveolar nerve block, especially in Pediatric Dentistry.